Thermal stability of the Mobil Five type metallosilicate molecular sieves - an in situ high, temperature X-ray diffraction study - Bhange, Deu S.; Ramaswamy, Veda (Materials Research Bulletin, 2007)
We have carried out in situ high temperature X-ray diffraction (HTXRD) studies of silicalite-1 (S-1) and metallosilicate molecular sieves containing iron, titanium and zirconium having Mobil Five (MFI) structure (iron silicalite-1 (FeS-1), titanium silicalite-1 (TS-1) and zirconium silicalite-1 (ZrS-1), respectively) in order to study the thermal stability of these materials. Isomorphous substitution of Si4+ by metal atoms is confirmed by the expansion of unit cell volume by X-ray diffraction (XRD) and the presence of Si-O-M stretching band at similar to 960 cm(-1) by Fourier transform infrared (FTIR) spectroscopy. Appearance of cristobalite phase is seen at 1023 and 1173 K in S-1 and FeS-1 samples. While the samples S-1 and FeS-1 decompose completely to cristobalite at 1173 and 1323 K, respectively, the other two samples are thermally stable upto 1623 K. This transformation is irreversible. Although all materials show a negative lattice thermal expansion, their lattice thermal expansion coefficients vary. The thermal expansion behavior in all samples is anisotropic with relative strength of contraction along `a' axes is more than along `b' and V axes in S- 1, TS-1, ZrS-1 and vice versa in FeS-1. Lattice thermal expansion coefficients (alpha(v)) in the temperature range 298-1023 K were -6.75 x 10(-6) K-1 for S-1, -12.91 x 10(-6) K-1 for FeS-1, -16.02 x 10(-6) K-1 for TS-1 and -17.92 x 10(-6) K-1 for ZrS-1. The highest lattice thermal expansion coefficients (alpha(v)) obtained were -11.53 x 10(-6) K-1 for FeS-1 in temperature range 298-1173 K, -20.86 x 10(-6) K-1 for TS-1 and -25.54 x 10(-6) K-1 for ZrS-1, respectively, in the temperature range 298-1623 K. Tetravalent cation substitution for Si4+ in the lattice leads to a high thermal stability as compared to substitution by trivalent cations. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: microporous materials; Thermal expansion; X-ray diffraction

Thermal expansion properties of stannosilicate molecular sieve with MFI type structure - Niphadkar, P. S.; Bhange, Deu S.; Selvaraj, K.; Joshi, P. N. (Chemical Physics Letters, 2012)
An in situ high temperature X-ray diffraction study was carried out for investigating the thermal expansion properties of Si-MFI and SnSi-MFI molecular sieves. The thermal stability up to 973 K and a negative lattice thermal expansion in anisotropic manner was exhibited by both the phases in the temperature range of 373-973 K. The trend observed in contraction along the axes was as: a > c > b. The substitution of Sn4+ in MFI framework resulted in an expansion of unit cell volume and in an increase in the lattice thermal expansion coefficient in the temperature range 423-973 K. (C) 2012 Elsevier B. V. All rights reserved.

TiO2 nanoparticles decorated on BiOCl flakes with enhanced visible light photocatalytic activity - Shinde, Deepali S.; Bhange, Pallavi D.; Jha, Ratnesh K.; Bhange, Deu S. (ChemistrySelect, 2020)
Facile preparation route for BiOCl and BiOCl/TiO2 nanocomposites with TiO2 nanoparticles decorated on BiOCl flakes via solution combustion method is reported in the present paper. Structural, textural and optical properties of the prepared materials are extensively studied using various physicochemical characterization tools such as X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), UV-vis spectroscopy (DRS), N-2 adsorption-desorption study (BET), photoluminescence spectroscopy (PL), etc. BiOCl/TiO2 nanocomposites show a red shift in the light absorption as compared to that of bare BiOCl which leads to the extended absorption in visible light region. Further photocatalytic experiments for Rhodamine B and phenol degradation demonstrate that the BiOCl/TiO2 nanocomposites have superior photocatalytic properties than bare BiOCl. Improved photocatalytic performance of BiOCl/TiO2 composites is attributed to the synergistic effect between BiOCl flakes and TiO2 nanoparticles, extended visible light absorption and delayed charge recombination.
Keywords: BiOCl; Hydoxyl radical evaluation; p-n heterojunction; phenol degradation; Photocatalysis; TiO2 nanocomposites